Nota sulla biblioteca psicologica di d’Annunzio - Zanoni, Andrea (Archivio d’Annunzio)
This contibution makes an initial survey of the books on psychological subjects conserved at the Vittoriale, showing some contacts between d’Annunzio’s writings and the psychoanalytic field of investigation.